Comparison of characteristics between Chinese diabetes mellitus-induced erectile dysfunction populations and non-diabetes mellitus-induced erectile dysfunction populations: A cross-sectional study - Peng, Jingxuan; Li, Dongjie; Liu, Longyun; Xiang, Yali; Tang, Yuxin (Frontiers in Endocrinology, 2022)
Background Erectile dysfunction (ED) is a common disease in adult men, and diabetes is an independent risk factor for ED. However, there are few reports on the distinction between diabetes mellitus-induced erectile dysfunction (DMED) and non-DMED features, as well as ED features of varying severity in the two groups. Methods A total of 365 ED patients treated at two clinics in China from 2019 to 2022 were included. Questionnaires of the International Index of Erectile Function (IIEF-5), Erectile Hardness Score (EHS), Premature Ejaculation Diagnostic Tool (PEDT), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7) were administered to the patients. They were divided into three groups according to the IIEF-5 score: 5-7 for severe ED, 8-11 for moderate ED, and 12-21 for mild ED. In addition, the patient’s age, weight, height, fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), total testosterone (TT) and other indicators were also collected. Statistical analysis was performed using SPSS 26, comparing all parameters between groups. Results Age (P<0.001), height (P=0.009), body mass index (BMI) (P=0.002), PEDT (P<0.001), FBG (P<0.001), FSH (P<0.001), TG (P<0.001), TT (P<0.001) and triglyceride-glucose index (TyG) (P<0.001) were significantly different between diabetic ED and nondiabetic ED subjects. The trend test in the nondiabetic ED population found a negative correlation between the IIEF-5 score and PHQ-9 (P for trend=0.15). Multivariate ordinal logistic regression in the diabetic ED population showed that elevated LH OR=11.37 (95% CI: 0.966, 3.897) and elevated PRL OR=4.10 (95% CI: 0.410, 2.411) were associated with an increased risk of more severe ED. Conclusions The aetiology, demographic parameters, degree of premature ejaculation, and related biochemical tests were significantly different between the DMED and non-DMED populations.